Організація самостійної роботи майбутніх інженерів у професійно орієнтованому навчанні іноземної мови - Бойко, Ганна Анатоліївна; Юрчук, Людмила Володимирівна (My University, 2026)
Стаття присвячена проблемі організації самостійної роботи здобувачів вищої освіти інженерних спеціальностей у процесі вивчення іноземної мови професійного спрямування. Визначено, що саме самостійна робота відіграє ключову роль у вихованні майбутнього інженера як незалежного студента і його підготовки до навчання впродовж життя у процесі вивчення іноземної мови професійного спрямування . Уточнено поняття самостійної роботи, як форми організації навчально-пізнавальної діяльності, що здійснюється під опосередкованим керівництвом викладача і вимагає від здобувача вищої освіти свідомого ставлення, рефлексії, самодисципліни та відповідальності. Проаналізовано мотиваційний, лінгвістичний, організаційний і професійно-прикладний компоненти самостійної роботи здобувачів освіти. Визначено, що відповідно до рівня самостійності навчальних дій здобувачів вищої освіти самостійна робота розподіляється на три види: репродуктивну, напівтворчу і творчу самостійну роботу. Охарактеризовано кожен з цих видів. Визначено, що у процесі реалізації репродуктивної самостійної роботи майбутні інженериопановують фахову лексику і здобувають навичок читання/ аудіювання і розуміння фахових текстів. Цей вид готує здобувачів до напівтворчої і творчої самостійної роботи. Напівтворча самостійна робота характеризується вищим ступенем самостійності і вищою творчою активністю. У процесі творчої самостійної роботи здобувачі вищої освіти пропонують власні вирішення проблемних ситуацій. Саме цей вид формує вміння вирішувати складні комунікативні завдання. І саме під час цієї роботи формується фахова самостійність майбутнього інженера. The article deals with the problem of organization of independent learning activities of higher education students of engineering specialties in the course of studying a professionally oriented foreign language. It has been defined that autonomous learning activities in particular play a key role in education of a prospective engineer as an independent student and his preparation for studies throughout life in the course of studying a professionally oriented foreign language. It has been specified the notion of independent activities as a form of educational- cognitive activities that is carried out indirectly under the guidance of a teacher and demands from a higher education student cognitive attitude, reflection, self-discipline and responsibility. It has been analyzed the motivating, linguistic, organizing and professionally-applied components of independent learning activities of higher education students. It has been defined that in accordance to the level of independence of learning activities of higher education students the autonomous learning activities is divided into three types: reproductive, half creative and creative independent activities. It has been described each of these types. It has been defined that in the course of reproductive independent learning activities the prospective engineers master the professional vocabulary and acquire skills of reading / auditing and understanding special texts. This type trains students to half creative and creative independent learning activities. Half creative independent learning activities is characterized by the highest degree of independence and the highest creative activity. In the course of creative independent learning activities higher education students propose their own solutions for resolving the problem situations. Precisely this type forms an ability to resolve the complex communicative tasks. And namely in the course of this activity the professional independence of a prospective engineer is formed.
Keywords: кафедра іноземних мов професійного спрямування; самостійна робота; іноземна мова професійного спрямування; репродуктивна самостійна робота; independent learning activities; prospective engineers in professionally oriented foreign language; reproductive independent learning activities